College algebra : - Barnett, Raymond A (McGraw-Hill Higher Education, 2005)
This book is to encourage students to investigate mathematical ideas and processes graphically and numerically, as well as algebraically. The book also provides a library of elementary functions, including their important properties and uses. Having this library of elementary functions as a basic working tool in their mathematical tool boxes, students will be able to move into calculus with greater confidence and understanding. In addition, this book gives the student substantial experience in solving and modeling real world problems. Enough applications are included to convince even the most skeptical student that mathematics is really useful. Most of the applications are simplified versions of actual real-world problems taken from professional journals and professional books.